2020
DOI: 10.1016/j.apenergy.2020.114856
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cooling loads in the wine industry and novel seasonal indicator for reliable assessment of energy saving through retrofit of chillers

Abstract: The food sector is a major consumer of energy and growing efforts are being made in the search for solutions that will guarantee the efficient and sustainable use of energy resources. Among the different sectors, wineries are attracting particular interest due to the continuous growth of the global market and production. Surveys conducted in the winemaking sector have highlighted the importance of performing accurate energy audits and have identified the installation of efficient refrigeration systems as a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…However, in the water temperature control of chillers, when the supply temperature of chilled water and the return temperature of cooling water are constantly set, the values of COP change with the variations of cooling load. The optimal COP value of chiller which normally does not appear at full-load condition, may flexibly fluctuate in a range (e.g., 70%–80%) of PLR curve [ 33 , 34 ]. The control logic for chiller sequencing/switch on/off control and water temperature control is to reach to the optimal COP value and obtain the optimal operation cost, on the basis of cooling load characteristics and cooling demand satisfaction.…”
Section: Operation Control Strategies For Hub Airport Terminalsmentioning
confidence: 99%
“…However, in the water temperature control of chillers, when the supply temperature of chilled water and the return temperature of cooling water are constantly set, the values of COP change with the variations of cooling load. The optimal COP value of chiller which normally does not appear at full-load condition, may flexibly fluctuate in a range (e.g., 70%–80%) of PLR curve [ 33 , 34 ]. The control logic for chiller sequencing/switch on/off control and water temperature control is to reach to the optimal COP value and obtain the optimal operation cost, on the basis of cooling load characteristics and cooling demand satisfaction.…”
Section: Operation Control Strategies For Hub Airport Terminalsmentioning
confidence: 99%
“…The study resulted in a reduction of energy consumption of 39.6%, when compared to a traditional room air conditioner. Catrini et al 36 performed a study on saving energy in the food industry, more specifically the wine industry. By retrofitting the chillers used in this assessment, it was concluded that the use of standard seasonal indicators leads to 56.9% and 83.9% overestimation of potential energy savings, for low and medium temperature cooling energy uses, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The assessment of the actual energy demands of the cellar is the first fundamental step for any proper energy audit. In the wine-making sector this is not an easy task because, as highlighted also in [13], the energy demands are strongly variable on seasonal and daily bases, and a direct measurement of the consumption of the many involved devices would be too expensive (the only available information on consumptions usually derives from monthly or annual bills). To this end, the main steps of the wine production have been deeply analyzed (Section 2.1) to obtain as accurate as possible consumption profiles of each step, and therefore of the entire process (Section 2.2).…”
Section: Wine Making Process and Associated Energy Demandsmentioning
confidence: 99%
“…where ϕ in,i (t) is the energy flow (power) associated with the main input to a unit (fuel), ϕ out,i (t) is the energy flow (power) associated with the main ouptut of the unit (product), ϕ MAX out,i and ϕ MIN out,i are the maximum and minimum loads of the unit, respectively, K1 i and K2 i are (usually positive) parameters depending on the type and features of the energy conversion unit, and δ i (t) is a binary variable that identifies the on/off status of the unit. When δ i (t) = 0, Equations (12) and (13) give ϕ i,out (t) = 0 and so Equation (11) gives ϕ i,in (t) = 0, i.e., the unit is off. When δ i (t) = 1, Equations (12) and (13) let ϕ i,out (t) vary within the range of possible loads and the fuel consumption is calculated by Equation (11), i.e., the unit is on.…”
Section: Operation Of Energy Conversion Unitsmentioning
confidence: 99%
See 1 more Smart Citation